Ferroptosis: A novel therapeutic strategy and mechanism of action in glioma - Zhang, Gaosen; Fang, Yi; Li, Xiang; Zhang, Zhen (Frontiers in Oncology, 2022)
Glioma is the most common malignant tumor of the central nervous system and resistance is easily developed to chemotherapy drugs during the treatment process, resulting in high mortality and a short survival in glioma patients. Novel therapeutic approaches are urgently needed to improve the therapeutic efficacy of chemotherapeutic drugs and to improve the prognosis of patients with glioma. Ferroptosis is a novel regulatory cell death mechanism that plays a key role in cancer, neurodegenerative diseases, and other diseases. Studies have found that ferroptosis-related regulators are closely related to the survival of patients with glioma, and induction of ferroptosis can improve glioma resistance to chemotherapy drugs. Therefore, induction of tumor cell ferroptosis may be an effective therapeutic strategy for glioma. This review summarizes the relevant mechanisms of ferroptosis, systematically summarizes the key role of ferroptosis in the treatment of glioma and outlines the relationship between ferroptosis-related ncRNAs and the progression of glioma.